ANALISIS KEMAMPUAN VISUALISASI SPASIAL MATEMATIS SISWA SMP BERBANTUAN APLIKASI BERBASIS AUGMENTED REALITY - Iwan Kusuma Wardana (Universitas Muhammadiyah Semarang, 2022)
This research was conducted with the aim of analyzing and describing the mathematical, spatial visualization abilities of junior high school students in class VIII in solving spatial geometry math problems with the help of augmented reality-based applications in the categories of high, medium, and ability students. The research was conducted at SMPN 3 Karawang Barat, with a descriptive qualitative method. The process of collecting data was carried out using the test and interview methods to the research subjects. The results of the research show that high mathematical spatial visualization skills have the characteristics of imagination, use of concepts, problem solving and pattern search that are quite good in solving problems. Then, the medium mathematical, spatial visualization ability has good imaginative characteristics. And those with low mathematical, spatial visualization skills have poor imagining characteristics, use of concepts, problem solving and pattern search and experience many difficulties in various cases.